Desenvolvimento de complexos a base de proantocianidinas de acácia negra (Acacia mearnsii) para uso na terapia do câncer de bexiga - Diz, Fernando Mendonça (2018)
Cisplatin is a metal complex widely used in the therapy of several cancers, but its use has numerous disadvantages related to its toxicity. This limitation has forced the search for new compounds that minimize these effects. Flavanoid metal complexes are potential candidates for becoming a potential cancer therapeutic agent. Proanthocyanidins (PAC) are polyphenols with well-studied antitumor activity, as well as binding sites for complexation with metal ions. In this context, the objective of this work was to synthesize metallic complexes with Ag, Cu and Pt based Black Wattle proanthocyanidins to evaluate its cytotoxic effect in bladder cancer cells. The synthesis was followed by characterization by FTIR, TGA, DRX and EDS to identify the presence of the metal in the complex. Cytotoxic evaluation allowed to observe that the silver and copper complexes did not promote any effect on tumor viability. However, the [PtPAC] complex promoted reduction of tumor viability, showed antiproliferative activity and selectivity against human bladder cancer cells. In addition, this complex was able to induce cell death by the apoptosis process.